Análise comparativa entre o conversor BUCK e o conversor ressonante LLC em drivers de leds visando aspectos industriais - Oliveira, Theyllor Hentschke de (2019)
This paper presents a quantitative design analysis, performance prediction and practical testing of buck and half-bridge LLC resonant converters as a solution for a power control stage in the realization of a 180 W driver applied to LED street lighting lamp. As a starting point of the proposal, a product of the Zagonel Ltda Company was used. Regulatory requirements for LED street lights lamps brought by INMETRO Portaria No. 20 stipulate operating conditions for the device. These conditions are connected to power quality, electromagnetic compatibility and luminous efficacy, being the last one directly linked to system efficiency, allowing the discussion of alternative topologies for traditional solutions. The resonant LLC half-bridge converter has been widely studied as a potential LED drive circuit, with the premise of increasing the switching frequency and consequent reduction of filter elements, provided by its transition conditions of zero voltage switching in the inverter and zero current switching in rectifier. In addition, this converter topology brings insulation through a high frequency transformer. However, the implementation of converters with more active and passive elements has greater design complexity than basic circuits like buck topology. The design parameters and main efficiency conditions of buck and half-bridge LLC resonant converters are reviewed in this work. The Buck converter was evaluated under 33 kHz, 60 kHz and 100 kHz, and the LLC Resonant converter was evaluated under 100 kHz, 140 kHz, 180 kHz and 220 kHz. The tests shows that the total efficiency of the converters is very close under some design conditions, indicating that the study of losses for each component is necessary. As fundamental characteristics of project realization, the costs and volumes occupied by the through role components present in booth solutions are also analyzed, highlighting the price disadvantage for the implemented resonant circuit solution.